Running economy after a low- and high-intensity training session in naturally menstruating endurance-trained female athletes: The FENDURA project - Docter, H.; Taylor, M.; Müller, A. L.; De Koning, J. J.; Sandbakk, Ø. B.; Osborne, J. O.; Noordhof, D. A. (Scandinavian Journal of Medicine & Science in Sports, 2025)
The ability to maintain running economy is generally evaluated during a long continuous exercise bouts, and it is unclear whether the menstrual cycle phase acts as a confounder. The first aim of this study was to evaluate the ability to maintain running economy during typical 1-h low- (LIT) and high-intensity training (HIT) sessions in female athletes. The second aim was to investigate whether menstrual cycle phase affected the ability to maintain running economy. Naturally menstruating endurance-trained females performed three LIT (n = 16) (45%-55% of the maximal velocity achieved during the maximal incremental test) and/or three HIT sessions (n = 17) (5 × 4 min at 80% of the maximal velocity achieved during the maximal incremental test) during three distinct menstrual cycle phases: early follicular, ovulatory, and mid luteal. Running economy was determined before and after each session. Running economy, expressed as energy cost (before: 1.34; after: 1.34 kcal/kg/km, p = 0.797) and oxygen cost (before: 272, after: 273 mL/kg/min, p = 0.348), was not significantly different before versus after the LIT session. Energy cost (before 1.33; after: 1.34 kcal/kg/km, p = 0.130) was not significantly different before versus after the HIT session, but oxygen cost (before: 269; after: 274 mL/kg/km, p < 0.003) was slightly higher after the session. Menstrual cycle phase did not confound the ability to maintain running economy. Running economy can be maintained during a typical 1-h LIT session. The ability to maintain running economy during a typical HIT session depends on the expression used; energy cost was unaffected, while oxygen cost may be slightly increased after HIT sessions.